Properties of Cassava Starch Modified by Amylomaltase from Corynebacterium glutamicum. Issue 6 (22nd April 2016) - Suriyakul Na Ayudhaya, Pitcha; Pongsawasdi, Piamsook; Laohasongkram, Kalaya; Chaiwanichsiri, Saiwarun
Abstract: Amylomaltase (α‐1, 4‐glucanotransferase, AM; EC 2.4.1.25) from Corynebacterium glutamicum expressed in Escherichia coli was used to prepare the enzyme‐modified cassava starch for food application. About 5% to 15% (w/v) of cassava starch slurries were incubated with 1, 3, or 5 units of amylomaltase/g starch. Apparent amylose, amylopectin chain length distribution, thermal properties, freeze–thaw stability, thermo‐reversibility, and gel strength of the obtained modified starches were measured. The apparent amylose content and retrogradation enthalpy were lower, whereas the retrogradation temperatures, freeze–thaw stability, and thermo‐reversibility were higher than those of the native cassava starch. However, when amylomaltase content was increased to 20 units of amylomaltase/g starch and for 24 h, the modified starch showed an improvement in the thermo‐reversibility property. When used in panna cotta, the gel strength of the sample using the 20 units/24 h modified cassava starch was similar to that of using gelatin.